Utilization of the Facebook Marketplace as a Marketing Media and Promotional Media in Improving the MSME Economy of Pottery Pot Crafts in Kemangsen Village - Nefrida Jandini; Poppy Febriana; Moh Ar Raafi Ahsa Febian; Muhammad Rafli Sadar Darmawan Siahaan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
This community service is entitled "Utilization of the Facebook Marketplace as a Marketing Media and Promotional Media in Increasing the Economy of MSMES for Pottery Pot Crafts in Kemangsen Village". Pottery pots are craft pots made of cement and clay which have various shapes. Kemangsen Village is known as a pot maker and seller village that has been making pots since 1998. Many residents make a living from producing these pots. In the village of Kemangsen there are many pot manufacturers who produce pots of various types and shapes. In 2020 or since the COVID-19 pandemic, the sales of MSMES in Kemangsen Village have decreased. In an era like now, people are familiar with social media and are also widely used as a medium for buying and selling online. Therefore, researchers want to advance the pot manufacturers in Kemangsen village so they are not left behind in this modern era. So the author provides innovation by selling on the Facebook marketplace (online market) as a media promotion and selling so that products from Kemangsen village can be recognized by the surrounding community as well as outsiders. This community service uses qualitative methods with a qualitative approach. Data collection techniques by interview, observation, and documentation with one of the informants of the pottery pot craftsmen, namely Mr. Wawan and the employee who worked on the making of the pot. The results of this community service show that pottery pot crafts in Kemangsen village are lacking in terms of online promotion and a lack of marketing education which has made the Kemangsen village economy decline. Because some of the people there work as earthenware pot craftsmen, therefore the author helps by educating about marketing and marketplaces (online markets) using the online media Facebook as an example of a marketplace (online market). Some of these activities can be used as examples for other villages in terms of selling Kemangsen village products so that many people can reach them.